2014
DOI: 10.1002/jbmr.2149
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Parathyroid Hormone-Related Protein (1–36) and Parathyroid Hormone (1–34) on Markers of Bone Turnover and Bone Density in Postmenopausal Women: The PrOP Study

Abstract: In [1], an author's name was spelled incorrectly. The correct author listing should appear as: Leila Khan.This erratum corrects the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Earlier, preliminary data collected in short-term and small human studies, (2)(3)(4) as well as preclinical studies, (5) had suggested that PTHrP might increase formation without increasing resorption and provided the rationale for the current randomized trial comparing two doses of PTHrP to teriparatide over 3 months. (1) The absence or near absence of hypercalcemia with comparable doses in those prior studies (2)(3)(4) also suggested that PTHrP might avoid that known potential side effect of PTH therapy.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…Earlier, preliminary data collected in short-term and small human studies, (2)(3)(4) as well as preclinical studies, (5) had suggested that PTHrP might increase formation without increasing resorption and provided the rationale for the current randomized trial comparing two doses of PTHrP to teriparatide over 3 months. (1) The absence or near absence of hypercalcemia with comparable doses in those prior studies (2)(3)(4) also suggested that PTHrP might avoid that known potential side effect of PTH therapy.…”
mentioning
confidence: 82%
“…Earlier, preliminary data collected in short-term and small human studies, (2)(3)(4) as well as preclinical studies, (5) had suggested that PTHrP might increase formation without increasing resorption and provided the rationale for the current randomized trial comparing two doses of PTHrP to teriparatide over 3 months. (1) The absence or near absence of hypercalcemia with comparable doses in those prior studies (2)(3)(4) also suggested that PTHrP might avoid that known potential side effect of PTH therapy.Horwitz and colleagues (1) show that, indeed, PTHrP has a net anabolic effect with a significant bone formation marker increase over the 3 months of the study. The net effects of PTHrP on BMD over 3 months were indistinguishable from those of teriparatide, although inferences about BMD are limited by the small study size and relatively short duration.…”
mentioning
confidence: 95%
See 3 more Smart Citations